2004
DOI: 10.1016/j.ejcts.2004.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Surgical results for active endocarditis with prosthetic valve replacement: impact of culture-negative endocarditis on early and late outcomes

Abstract: In our analysis, no independent adverse predictor was detected for hospital death; however, culture-negative endocarditis was identified as an independent predictor for both late survival and events after surgery. Event-free survivals were similar between staphylococcus infection and culture-negative endocarditis, and all events occurred within 2 years after operation, suggesting the necessity of close follow-up during that period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 23 publications
3
30
1
Order By: Relevance
“…The present study, consistently with a number of previous analyses [1215], showed that 2 out of the 6 most significant independent predictors of postoperative death in 440 endocarditis surgery patients were specific of the IE setting, that is, microbiology- or infection-related, and not included in the most commonly employed prognostic systems. …”
Section: Discussionsupporting
confidence: 89%
“…The present study, consistently with a number of previous analyses [1215], showed that 2 out of the 6 most significant independent predictors of postoperative death in 440 endocarditis surgery patients were specific of the IE setting, that is, microbiology- or infection-related, and not included in the most commonly employed prognostic systems. …”
Section: Discussionsupporting
confidence: 89%
“…However, blood cultures remain negative in 14–30%1–5 11 25 of cases often delaying the initiation of treatment, with a potential profound impact on clinical outcome 26 27. In a study of patients undergoing surgical treatment for IE, negative blood cultures were independently associated with an adverse outcome after surgery 28 29. Negative blood cultures are, therefore, of considerable concern in the management of these patients, and may result from inadequate microbiological techniques, infection with highly fastidious bacteria or non-bacterial pathogens, or the earlier administration of antimicrobial agents before blood cultures were obtained 12.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of patients post-surgery, multivariate analysis of variables influencing events (death, peri-prosthetic leakage, re-operation and recurrence of infection) identified those patients with negative blood cultures as significantly more likely to suffer an adverse outcome after surgery compared with those patients where a pathogen had been identified (52.4% vs. 19.6%, P < 0.05) [10]. Negative blood cultures are, therefore, of considerable concern in the management of IE patients.…”
Section: Introductionmentioning
confidence: 97%